75 Infective endocarditis and intravenous drug use: a descriptive study. (June 2018) - Straw, Sam; Baig, Wazir; Gillott, Richard; Pirone, Francesco; Sandoe, Jonathan
Abstract : Background: Intravenous drug use (IVDU) is a recognised predisposition for the development of infective endocarditis (IE). There is controversy regarding surgery for these patients because of relapse due to non-compliance with medical therapy and recurrence due to ongoing IVDU. This study aims to describe the outcomes in a large cohort of patients referred to a single tertiary centre. Methods: Between 01/01/06 and 31/12/16 consecutive patients referred to the endocarditis multidisciplinary team were identified from our electronic database. Patients were included if they were either Duke's confirmed or Duke's possible and treated for IE and IVDU within 90 days. Affected valves and microorganisms were recorded, as well as indications for, type and number of operations. Outcomes were relapse (re-infection with same microorganism within 1 year), recurrence (infection with different organism, or same organism beyond 1 year), further surgical intervention and all-cause mortality. Results: In total, there were 105 episodes in 92 patients; 92 episodes were Duke's definite, and 13 Duke's possible. The incidence of IE varied considerably year-on-year, but median age increased. Staphylococcus aureus (59) was the most frequently observed pathogen, followed by Streptococcus spp. (31), Enterococcus spp. (8), S taphylococcus. epidermidis (2), Candida spp. (2), Pseudomonas aeruginosa (1) and Corynebacterium diphtheriae (1). 7 episodes (6.67%) were culture negative. Ninety-one episodes affected native values and 10, prosthetic valves. More episodes affected left sided structures (78) than right (40) and the mitral valve was most commonly implicated (42), followed by tricuspid (38), aortic (36) and pulmonary (2). Pacemaker lead infection occurred in one patient. Forty-eight (45.7%) episodes required surgery; bioprosthetic valves for left sided disease were commonest with 17 aortic and 10 mitral valves compared to 6 and 8 mechanical valves respectively. Intervention for right sided disease was uncommon, with only 8 bioprosthetic tricuspid valves and one abandoned attempt at pulmonary valve surgery. Only one patient underwent further surgery following late recurrence with S. epidermidis affecting a bioprosthetic mitral valve. Three (3.26%) patients relapsed, 1 patient relapsed twice. 12 (13.0%) patients had recurrence, one patient had two recurrences. All-cause mortality was 4.35% at 30 days, 26.4% at 1 year and 36.4% at 3 years. Unadjusted mortality was higher in patients who underwent surgery, reflecting differences at baseline. Implications: Contrary to common perception, IE in IVDU patients affected left sided structures more commonly than and right and surgery was commonly indicated. The rate of relapse was low, but the recurrence rate was high. All-cause mortality following an episode of IE is high, and so surgery remains controversial, especially in patients who continue IVDU.